Composite silicon-based material and preparation method and application thereof

By combining the conductive carbon layer on the surface of the silicon-based anode material and forming a buffer space, the problem of volume expansion and insufficient conductivity of the silicon-based anode material during lithium storage is solved, and the effects of high cycling performance and low capacity attenuation are achieved.

CN115101732BActive Publication Date: 2025-03-04SHENZHEN DYNANONIC CO LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202210738993.7
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2022-06-27
Publication Date
2025-03-04
Estimated Expiration
2042-06-27

AI Technical Summary

Technical Problem

The existing silicon-based anode materials have severe volume expansion effects, poor conductivity and unstable SEI film during lithium storage, resulting in problems with the cyclic stability and capacity attenuation of the electrode.

Method used

By combining a conductive carbon layer on the surface of the silicon base and forming a buffer space between the conductive carbon layer and the silicon base, a composite silicon-based material is formed to alleviate the volume expansion effect and improve the conductive performance.

Benefits of technology

The composite silicon-based material has stable structure during lithium storage, high cycling and rate performance, and low capacity attenuation, which significantly improves the deformation resistance and electrochemical performance of the electrode.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN115101732B_ABST
    Figure CN115101732B_ABST
Patent Text Reader

Abstract

The present application discloses a composite silicon-based material, a preparation method and an application thereof. The composite silicon-based material of the present application includes a silicon base body and a conductive carbon layer, which are combined with the conductive carbon layer and a buffer space is formed between the two. The buffer space provided between the conductive carbon layer and the surface of the silicon base body of the composite silicon-based material of the present application can effectively alleviate the deformation effect of the composite silicon-based material during the lithium storage process, improve the cycle performance of the composite silicon-based material, and reduce the capacity attenuation; and the conductive carbon layer effectively improves the conductivity and rate performance of the composite silicon-based material. In addition, the preparation method of the composite silicon-based material can ensure the stable performance and high efficiency of the composite silicon-based material, saving production costs.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application belongs to the technical field of negative electrode materials, and specifically relates to a composite silicon-based material and a preparation method and application thereof. Background Art

[0002] Lithium-ion batteries are widely used in many fields such as 3C electronic products, power vehicles and energy storage power stations due to their high energy density, low self-discharge, no memory effect and long cycle life.

[0003] With the rapid development of electric vehicles and large-scale energy storage equipment, the requirements for lithium-ion batteries, which play a key role in them, are becoming increasingly higher. High energy density, long cycle life and high safety are the main indicators pursued by the next generation of lithium-ion batteries. However, the current commercial lithium-ion battery negative electrode material - graphite, has a capacity close to its theoretical capacity (375mAh / g), which is difficult to improve further. In addition, the lithium insertion potential of graphite is very close to the deposition potential of lithium. Lithium precipitation is very likely to occur under fast charging and low temperature environments, causing safety hazards. Therefore, exploring high-performance negative electrode materials has become the key to the development of the next generation of lithium-ion batteries.

[0004] Silicon-based negative electrodes have attracted the attention of many researchers due to their high theoretical specific capacity. At the same time, the lithium insertion potential of silicon is slightly higher than that of graphite, which is relatively safer. In addition, silicon is abundant in the earth and is low-cost, making it suitable for large-scale production. However, silicon-based materials, as negative electrodes for the next generation of lithium-ion batteries, also face many problems: the most important and urgent problem to be solved is that the severe volume expansion effect of silicon during lithium storage will cause the electrode material to pulverize or even fall off, resulting in poor cycle stability of the electrode; secondly, silicon is a semiconductor with poor intrinsic conductivity, and it needs to be modified to improve its electrochemical performance; the SEI film on the silicon negative electrode is unstable, and the low coulombic efficiency of the electrode further exacerbates the capacity decay of the electrode. Summary of the invention

[0005] The purpose of the present application is to overcome the deficiencies of the above-mentioned prior art and to provide a composite silicon-based material and a preparation method thereof, so as to solve the technical problems of the existing silicon-based negative electrode materials such as serious volume expansion effect and poor electrical conductivity.

[0006] Another object of the present application is to provide a negative electrode and a secondary battery containing the negative electrode to solve the technical problems of rapid capacity decay and unsatisfactory cycle performance of existing secondary batteries.

[0007] In order to achieve the above application purpose, the first aspect of the present application provides a composite silicon-based material. The composite silicon-based material of the present application comprises a silicon base body and a conductive carbon layer, wherein the conductive carbon layer is bonded to the surface of the silicon base body, and a buffer space is formed between the silicon base body and the conductive carbon layer.

[0008] The second aspect of the present application provides a method for preparing the composite silicon-based material of the present application. The method for preparing the composite silicon-based material of the present application comprises the following steps:

[0009] Providing a silicon base body;

[0010] forming a film layer on the surface of the silicon substrate;

[0011] Forming a conductive carbon layer on the outer surface of the film layer;

[0012] The film layer is removed, so that the conductive carbon layer is combined on the surface of the silicon base body, and a buffer space is formed between the conductive carbon layer and the silicon base body to obtain a composite silicon-based material.

[0013] In a third aspect of the present application, a negative electrode is provided. The negative electrode of the present application comprises the composite silicon-based material of the present application.

[0014] In a fourth aspect of the present application, a secondary battery is provided, which includes a negative electrode, and the negative electrode is the negative electrode of the present application.

[0015] Compared with the prior art, this application has the following technical effects:

[0016] The composite silicon-based material of the present application combines the conductive carbon layer with the surface of the silicon base body, and the combination of the two is stable; and the buffer space set between the conductive carbon layer and the surface of the silicon base body can effectively alleviate the volume expansion effect of the composite silicon-based material during the lithium storage process, thereby effectively improving the anti-deformation effect ability of the composite silicon-based material of the present application, and improving the cycle performance of the composite silicon-based material; and the presence of the conductive carbon layer effectively improves the conductivity of the composite silicon-based material. Therefore, the synergistic effect of the silicon base body and the conductive carbon layer, as well as its unique buffer structure, endow the composite silicon-based material of the present application with good structural stability, high cycle performance and rate performance, and low capacity attenuation.

[0017] The composite silicon-based material preparation method of the present application can ensure that the prepared composite silicon-based material has the structural characteristics of the composite silicon-based material of the present application, and has high structural stability, deformation resistance and cycle performance. In addition, the composite silicon-based material preparation method of the present application can effectively ensure that the prepared composite silicon-based material has stable electrochemical performance and high efficiency, saving production costs.

[0018] Since the negative electrode of the present application contains the composite silicon-based material of the present application, the negative electrode of the present application has a stable structure during the lithium storage process, high cycle performance and rate performance, and low capacity attenuation.

[0019] Since the secondary battery of the present application contains the negative electrode of the present application, the secondary battery of the present application has high specific capacity, high rate performance, and excellent cycle performance. BRIEF DESCRIPTION OF THE DRAWINGS

[0020] In order to more clearly illustrate the specific implementation methods of the present application or the technical solutions in the prior art, the drawings required for use in the specific implementation methods or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are some implementation methods of the present application. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying any creative work.

[0021] Figure 1 This is a schematic diagram of the structure of the composite silicon-based material according to an embodiment of the present application;

[0022] Figure 2 This is a flowchart of a method for preparing a composite silicon-based material according to an embodiment of the present application;

[0023] Figure 3 This is a schematic diagram of the process of preparing the composite silicon-based material according to an embodiment of the present application;

[0024] Figure 4 This is a rate performance diagram of a battery assembled from a composite silicon-based material according to an embodiment of the present application;

[0025] Figure 5 This is a graph showing the cycle performance of a battery assembled from a composite silicon-based material according to an embodiment of the present application. DETAILED DESCRIPTION

[0026] In order to make the technical problems, technical solutions and beneficial effects to be solved by the present application more clearly understood, the present application is further described in detail below in conjunction with the embodiments. It should be understood that the specific embodiments described herein are only used to explain the present application and are not used to limit the present application.

[0027] In this application, the term "and / or" describes the association relationship of associated objects, indicating that there may be three relationships. For example, A and / or B can mean: A exists alone, A and B exist at the same time, and B exists alone. A and B can be singular or plural. The character " / " generally indicates that the associated objects are in an "or" relationship.

[0028] In this application, "at least one" means one or more, and "plurality" means two or more. "At least one of the following" or similar expressions refers to any combination of these items, including any combination of single items or plural items. For example, "at least one of a, b, or c", or "at least one of a, b, and c" can all mean: a, b, c, ab (i.e., a and b), ac, bc, or abc, where a, b, c can be single or multiple, respectively.

[0029] It should be understood that in the various embodiments of the present application, the size of the serial numbers of the above-mentioned processes does not mean the order of execution, some or all of the steps can be executed in parallel or sequentially, and the execution order of each process should be determined by its function and internal logic, and should not constitute any limitation on the implementation process of the embodiments of the present application.

[0030] The terms used in the embodiments of the present application are only for the purpose of describing specific embodiments, and are not intended to limit the present application. The singular forms "a", "said" and "the" used in the embodiments of the present application and the appended claims are also intended to include plural forms, unless the context clearly indicates other meanings.

[0031] The weight of the relevant components mentioned in the embodiment description of the present application can not only refer to the specific content of each component, but also represent the proportional relationship between the weights of the components. Therefore, as long as the content of the relevant components is proportionally enlarged or reduced according to the embodiment description of the present application, it is within the scope disclosed in the embodiment description of the present application. Specifically, the mass described in the embodiment description of the present application can be a mass unit known in the chemical industry such as μg, mg, g, kg, etc.

[0032] The terms "first" and "second" are used only for descriptive purposes to distinguish objects such as substances from each other, and should not be understood as indicating or implying relative importance or implicitly indicating the number of indicated technical features. For example, without departing from the scope of the embodiments of the present application, the first XX may also be referred to as the second XX, and similarly, the second XX may also be referred to as the first XX. Thus, the features defined as "first" and "second" may explicitly or implicitly include one or more of the features.

[0033] In the first aspect, the embodiment of the present application provides a composite silicon-based material. The composite silicon-based material of the embodiment of the present application includes a silicon base and a conductive carbon layer, and the conductive carbon layer is combined on the surface of the silicon base, and a buffer space is provided between the silicon base and the conductive carbon layer. Due to the existence of the buffer space between the conductive carbon layer and the surface of the silicon base, when the composite silicon-based material of the embodiment of the present application is in the process of lithium storage, the buffer space provides expansion space for the volume expansion of the silicon base, thereby significantly alleviating the volume expansion effect of the composite silicon-based material of the embodiment of the present application during the lithium storage process, giving the composite silicon-based material of the embodiment of the present application a high anti-deformation effect, and improving the cycle performance of the composite silicon-based material. Due to the presence of the conductive carbon layer, the conductivity of the composite silicon-based material is effectively improved, giving it a high rate performance. Therefore, the synergistic effect of the silicon base and the conductive carbon layer, as well as the unique buffer structure, give the composite silicon-based material of the embodiment of the present application a good structural stability, strong resistance to volume deformation, high cycle performance and rate performance, and low capacity attenuation.

[0034] In the embodiment, the conductive carbon layer and the silicon base body can be combined by the van der Waals force and surface tension generated by the two, specifically by the van der Waals force and surface tension of the relative surfaces of the two. Due to the combination between the silicon base body and the conductive carbon layer, the buffer space contained in the composite silicon-based material of the embodiment of the present application is formed by the van der Waals force and surface tension of the relative surfaces of the silicon base body and the conductive carbon layer. The conductive carbon layer combined by the van der Waals force and surface tension is stably combined with the silicon base body, and the buffer space is given elasticity, thereby enhancing its buffering effect as a volume expansion of the silicon base body, thereby further alleviating the volume expansion effect of the composite silicon-based material of the embodiment of the present application during the lithium storage process, and improving the high anti-deformation effect of the composite silicon-based material of the embodiment of the present application; when the composite silicon-based material stops storing lithium, the silicon-based composite material still maintains a complete sandwich structure without obvious deformation, which can further significantly improve the cycle performance of the composite silicon-based material.

[0035] In addition, the morphology and structure of the silicon base body and the conductive carbon layer contained in the composite silicon-based material according to the embodiment of the present application determine the overall morphology or structural characteristics of the composite silicon-based material. As in the embodiment, the silicon base body has two opposite surfaces, and a conductive carbon layer is bonded to at least one of the surfaces. Specifically, the conductive carbon layer may be bonded to one of the surfaces of the silicon base body through the above-mentioned van der Waals force and surface tension, or the conductive carbon layer may be bonded to the oppositely arranged surfaces through the above-mentioned van der Waals force and surface tension.

[0036] As in a further embodiment, the structure of the composite silicon-based material is as Figure 1 As shown, the silicon base body is a silicon substrate 1, and conductive carbon layers 2 are respectively bonded to two opposite surfaces of the silicon substrate 1, and there is a buffer space 3 between each conductive carbon layer 2 and the surface of the silicon base body, that is, the silicon substrate 1, which is formed by the above-mentioned van der Waals force and surface tension.

[0037] Figure 1 The structural features of the composite silicon-based material shown are only examples of one structure of the composite silicon-based material in the embodiment of the present application. Based on the bonding relationship between the silicon base body and the conductive carbon layer contained in the composite silicon-based material in the embodiment of the present application, the composite silicon-based material in the embodiment of the present application has the following structure: Figure 1 In addition to the structure shown, other structures may be used, such as a silicon base body that is a column, and a conductive carbon layer that is coated on the surface of the silicon base body.

[0038] Regardless of the morphology of the present application, the structure of the composite silicon-based material in each of the above embodiments forms a buffer space between the silicon base body and the conductive carbon layer, and the buffer space can provide a volume expansion space for the silicon base body to expand, thereby improving the structural stability of the composite silicon-based material, and further improving the deformation ability of the composite silicon-based material to resist volume expansion, thereby improving its cycle performance. At the same time, the presence of the conductive carbon layer can play a conductive modification role in the composite silicon-based material. After forming an electrode active layer, it can form a conductive connection, further improving the conductive performance of the composite silicon-based material, thereby improving the rate performance of the composite silicon-based material.

[0039] Based on the structures of the composite silicon-based materials in the above embodiments, the size of the silicon-based body contained in the composite silicon-based material can be adjusted according to the needs of actual applications. For example, when the silicon-based body is Figure 1 When the silicon substrate 1 is shown in FIG. , the thickness of the silicon substrate 1 may be 5-200 μm.

[0040] In the embodiment, the silicon base body contained in the composite silicon-based material is specifically as follows Figure 1 The material of the silicon substrate 1 may include at least one of a single substance and a silicon-based oxide, wherein the silicon-based oxide may be SiO x , SiO and SiO2, etc., SiO x Where x is 0.1 to 2. These silicon-based materials have high capacity.

[0041] In the embodiment, the thickness of the conductive carbon layer contained in the composite silicon-based material can be 50nm-5μm. By controlling the thickness of the conductive carbon layer, its mechanical properties against volume expansion of the silicon-based body can be improved, while its conductivity can be improved, the resistance of the composite silicon-based material can be reduced, and its rate performance can be improved.

[0042] In a specific embodiment, the material of the conductive carbon layer may include at least one of graphene, amorphous carbon, carbon nanotubes and graphite carbon. These materials have excellent electrical conductivity. For example, when it is graphene, its electrical conductivity is several orders of magnitude higher than that of redox graphene and activated carbon, which can greatly improve the electrical conductivity of the electrode, thereby improving the electrochemical performance of the electrode material. Moreover, the conductive carbon layer formed by these materials has good mechanical properties, thereby improving the ability to resist the volume expansion of the silicon base body, thereby improving the structural stability and cycle performance of the composite silicon-based material.

[0043] Since the buffer space contained in the composite silicon-based material is formed between the conductive carbon layer and the silicon base body, it can be formed by the combination of van der Waals force and surface tension. In the embodiment, the thickness of the buffer space along the vertical direction between the conductive carbon layer and the surface of the silicon base body can be 50nm-5μm. In addition, since the morphology of the buffer space can be designed by the morphology of the bonding surface between the conductive carbon layer and the silicon base body. As in the embodiment, when the surfaces of the conductive carbon layer and the silicon base body relative to each other have a certain extended plane or curved surface, the buffer space can be a buffer space layered structure morphology. Specifically, when the composite silicon-based material is a silicon substrate as shown in 1, the buffer space formed between the silicon substrate and the conductive carbon layer is a buffer space layered structure morphology. At this time, the thickness of the buffer space layer can be 50nm-5μm. The buffer space in this range fully plays the role of buffering the volume expansion of the silicon-based material, giving the composite silicon-based material the effect of structural stability and high cycle performance.

[0044] It can be seen from the above embodiments that the silicon base body and the conductive carbon layer contained in the composite silicon-based material of the embodiment of the present application have a synergistic effect, which can improve its conductivity. At the same time, the unique buffer structure effectively alleviates the deformation effect of the silicon base body during the lithium storage process. Through the joint action between the silicon base body and the conductive carbon layer, the composite silicon-based material of the embodiment of the present application is endowed with good structural stability, high cycle performance and rate performance, and low capacity attenuation. Moreover, the corresponding electrochemical performance of the composite silicon-based material of the embodiment of the present application can be improved by controlling and adjusting the structural morphology, material, thickness of the silicon base body and the conductive carbon layer, and the buffer space formed between the two.

[0045] In a second aspect, the present application also provides a method for preparing the composite silicon-based material of the present application. The process flow of the method for preparing the composite silicon-based material of the present application is as follows: Figure 2 and 3 As shown, the following steps are included:

[0046] S01: providing a silicon base body;

[0047] S02: forming a film layer on the surface of the silicon base body;

[0048] S03: forming a conductive carbon layer on the outer surface of the film layer;

[0049] S04: removing the film layer, so that the conductive carbon layer is combined with the surface of the silicon base body, and a buffer space is formed between the conductive carbon layer and the silicon base body, thereby obtaining a composite silicon-based material.

[0050] In step S01, the silicon base body is the silicon base body contained in the composite silicon-based material of the above-mentioned embodiment of the application, and specifically can be as follows: Figure 1The silicon substrate 1 is shown. Therefore, the morphology and material of the silicon base body in step S01 are as described above for the silicon base body contained in the composite silicon-based material in the embodiment of the present application.

[0051] The film layer formed in step S02 is formed by the buffer space contained in the composite silicon-based material of the above-mentioned application embodiment. Figure 1 The film layer of the buffer space 3 shown. Therefore, it needs to be removed in step S04. Then the material of the film layer is any material that can be removed in step S04 and does not affect the silicon base body and the conductive carbon layer. It is within the scope disclosed in the specification of this application. As in the embodiment, the material of the film layer is any one of metals and metal oxides. In a specific embodiment, the metal material can include any one of aluminum, iron, nickel, copper, zinc, etc. or an alloy of at least two of them. Then the metal oxide can be the metal oxide corresponding to these metals. These metals or metal oxides are convenient for forming film layers, and are easy to be removed, and will not adversely affect the silicon base body and the conductive carbon layer. Of course, based on the role of the film layer, its material can also be other materials.

[0052] When the material of the film layer is a metal material, the film layer can be formed by a deposition method, such as cathode magnetron sputtering, plasma spraying, chemical vapor deposition, electrochemical deposition, etc. When these deposition methods are used, the deposition temperature can be 25-1200° C. and the time can be 0.1-24 hours.

[0053] In addition, the thickness of the film layer can be controlled by controlling the conditions for forming the film layer, for example, the thickness of the film layer can be controlled to be 5-200 μm.

[0054] In step S03, the conductive carbon layer formed is the conductive carbon layer contained in the composite silicon-based material of the above-mentioned embodiment of the application, and can be specifically as follows: Figure 1 The conductive carbon layer 2 is shown. Therefore, the morphology and material of the conductive carbon layer in step S03 are as described above for the conductive carbon layer contained in the composite silicon-based material in the embodiment of the present application.

[0055] The method for forming the conductive carbon layer in step S03 can be selected according to the properties of the conductive carbon layer material. In an embodiment, the method for forming the conductive carbon layer on the outer surface of the film layer includes at least one of chemical vapor deposition and spray pyrolysis.

[0056] When the conductive carbon layer is formed by chemical vapor deposition, in the embodiment, the method for forming the conductive carbon layer on the outer surface of the film layer is chemical vapor deposition, which includes the following steps:

[0057] The precursor carbon source is subjected to thermal cracking treatment to generate carbon, and a conductive carbon layer is in-situ grown on the surface of the film layer and the silicon base body.

[0058] Among them, the precursor carbon source can be introduced into the reaction chamber together with the carrier gas, wherein the flow rate of the precursor carbon source can be 50-400mm / Hg, and the carrier gas can be a hydrogen-argon mixture with a flow rate ratio of 1:2 to 1:10. The temperature when the conductive carbon layer such as the graphene carbon layer is grown in situ can be 700-1200°C, and the time can be 0.5-6h. The distance between the precursor carbon source at the thermal cracking treatment site and the surface of the film layer can be 15-25cm, so as to control the temperature of the two temperature zones so that the conductive carbon layer is uniformly nucleated and grown on the surface of the film layer. In addition, the precursor carbon source can be gaseous or / and powder. In a specific embodiment, the precursor carbon source can include at least one of methane, ethylene, acetylene, ethanol, benzene, toluene, polymethyl methacrylate, polypropylene, polyethylene, polystyrene, polyethylene glycol and camphor balls. The thickness of the conductive carbon layer and other factors are adjusted by adjusting the relevant conditions of the chemical vapor deposition method, such as the flow rate of the precursor carbon source, the deposition spacing, the deposition temperature and time.

[0059] In step S04, after removing the film layer, the conductive carbon layer is bonded to the surface of the base body, and a gap is formed between the silicon base body and the conductive carbon layer to form the buffer space contained in the composite silicon-based material. Figure 1 The buffer space 3 shown. As in the embodiment, due to the characteristics of the silicon matrix and the conductive carbon layer themselves, the silicon matrix and the conductive carbon layer are combined through the van der Waals force and surface tension of the relative surfaces of the two, and the buffer space is formed between the silicon matrix and the conductive carbon layer. When the film layer is a metal layer, the method for removing the film layer includes an acid etching method. For example, the composite material deposited with the conductive carbon layer is immersed in an acid solution, so that the metal reacts with the acid to remove the metal film layer, thereby forming the buffer space. In the embodiment, the acid solution may include at least one of nitric acid, sulfuric acid, hydrochloric acid, phosphoric acid and acetic acid. However, it should be understood that the acid solution is only for removing the film layer and should not cause adverse damage to the conductive carbon layer and the silicon matrix.

[0060] The above-mentioned method for preparing the composite silicon-based material of the embodiment of the present application can ensure that the prepared composite silicon-based material has the structural characteristics of the composite silicon-based material of the embodiment of the present application, and has high structural stability and cycle performance. In addition, the method for preparing the composite silicon-based material of the present application can effectively ensure that the prepared composite silicon-based material has stable electrochemical performance, high efficiency, and saves production costs.

[0061] In the third aspect, the embodiment of the present application also provides a negative electrode. The negative electrode of the embodiment of the present application contains the composite silicon-based material of the embodiment of the present application. Specifically, the composite silicon-based material can be directly used as the negative electrode. In this way, the negative electrode of the embodiment of the present application has a stable structure during the lithium storage process, high cycle performance and rate performance, and low capacity attenuation.

[0062] Fourthly, the embodiment of the present application also provides a secondary battery. The secondary battery of the embodiment of the present application includes necessary components such as a positive electrode sheet, a negative electrode sheet, a separator and an electrolyte, and of course other necessary or auxiliary components. Among them, the negative electrode sheet is the negative electrode of the above-mentioned embodiment of the present application, that is, the negative electrode sheet contains the composite silicon-based material of the above-mentioned embodiment of the text application. Since the secondary battery of the embodiment of the present application contains the composite silicon-based material of the above-mentioned embodiment of the text application, the secondary battery of the embodiment of the present application has a high specific capacity, high rate performance, and excellent cycle performance.

[0063] The composite silicon-based material and its preparation method according to the embodiment of the present application are illustrated below through a number of specific embodiments.

[0064] 1. Composite silicon-based material and preparation method thereof Example:

[0065] Example A1

[0066] This embodiment provides a composite silicon-based material and a preparation method thereof. The composite silicon-based material includes a silicon wafer and a graphene layer bonded to two surfaces of the silicon wafer, forming a sandwich structure of graphene layer / silicon wafer / graphene layer, and the graphene layer is bonded to the surface of the silicon wafer, and a buffer space is formed between the two.

[0067] The method for preparing the composite silicon-based material comprises the following steps:

[0068] S1. Preparation of copper / silicon / copper precursor: A silicon wafer with a thickness of 8 μm was selected as the raw material, and metal pre-deposition was performed on both sides of the silicon wafer by cathode magnetron sputtering: a copper sheet with a size of Φ60 mm was selected as the target material, the target-substrate distance was 90 mm, and the vacuum degree was 3×10 -4 Pa, the working gas pressure (Ar) is 2Pa, the DC power supply sputtering power is 20W, the sputtering time is 100s, and the thickness of the pre-deposited copper layer is 50μm;

[0069] S2. Preparation of graphene / copper / silicon / copper / graphene intermediates: A graphene layer is uniformly grown on the surface of the precursor metal substrate prepared in step S1 by chemical vapor deposition. The pyrolysis carbon source of graphene is methane. During the introduction of a hydrogen-argon mixed gas with a flow rate ratio of 1:2, methane gas with a flow rate of 20 mm / Hg is introduced simultaneously. The precursor is placed in the middle of a tubular furnace chamber and reacted at 800°C for 5 hours; the thickness of the conductive carbon layer on the surface of the copper layer is 50 nm.

[0070] S3. Constructing a graphene-silicon-graphene hollow structure: The intermediate prepared in step S2 was subjected to acid etching treatment using 1 mol / L sulfuric acid, and the intermediate was immersed in sulfuric acid for 6 hours to remove the copper layer of the intermediate interlayer, and then the composite silicon-based material of this embodiment was prepared by centrifugation. It was measured that the thickness of the buffer space between the graphene layer and the silicon-based body was 500 nm.

[0071] Example A2

[0072] The present embodiment provides a composite silicon-based material and a preparation method thereof. The composite silicon-based material comprises a silicon wafer and a carbon nanotube layer bonded to two surfaces of the silicon wafer, forming a sandwich structure of carbon nanotube layer / silicon wafer / carbon nanotube layer, and the carbon nanotube layer is bonded to the surface of the silicon wafer, and a buffer space is formed between the two.

[0073] The method for preparing the composite silicon-based material comprises the following steps:

[0074] S1. Preparation of nickel / silicon / nickel precursor: A silicon wafer with a thickness of 20 μm was selected as the raw material, and metal pre-deposition was performed on both sides of the silicon wafer by chemical vapor deposition: a nickel sheet with a size of Φ40 mm was selected as the target electrode, and the vacuum degree was 5×10 -3 Pa, the working gas pressure (Ar) is 44Pa, the microwave filament current is 0.2A, and the voltage is adjusted from the starting voltage of 60V until the glow gradually turns blue, indicating that nickel ions enter the plasma, and the voltage is maintained at 900V for steady-state deposition for 2h. The thickness of the pre-deposited nickel layer is 80μm.

[0075] S2. Preparation of carbon nanotube / nickel / silicon / nickel / carbon nanotube intermediate: Use chemical vapor deposition to uniformly grow a carbon nanotube layer on the surface of the precursor metal substrate prepared in step S1. The pyrolysis carbon source of the carbon nanotube is ethanol. Place ethanol and the precursor in the upper and middle heating furnace chambers respectively. While introducing a hydrogen-argon mixed gas with a flow rate ratio of 1:5, react at 600°C for 12 hours; make the thickness of the conductive carbon layer on the surface of the nickel layer 3μm.

[0076] S3. Constructing a carbon nanotube-silicon-carbon nanotube hollow structure: The intermediate prepared in step S2 was subjected to acid etching treatment using a mixed acid solution of 1 mol / L sulfuric acid and 2 mol / L hydrochloric acid, and the intermediate was immersed in the mixed acid solution for 9 hours to remove the nickel layer of the intermediate interlayer, and then the composite silicon-based material of this embodiment was prepared by centrifugation. It was measured that the thickness of the buffer space between the carbon nanotube layer and the silicon-based body was 4 μm.

[0077] Example A3

[0078] The present embodiment provides a composite silicon-based material and a preparation method thereof. The composite silicon-based material includes a silicon wafer and a graphene layer bonded to two surfaces of the silicon wafer, forming a sandwich structure of amorphous carbon / silicon wafer / amorphous carbon, and the amorphous carbon layer is bonded to the surface of the silicon wafer, and a buffer space is formed between the two.

[0079] The method for preparing the composite silicon-based material comprises the following steps:

[0080] S1. Preparation of zinc oxide / silicon / zinc oxide precursor: A silicon wafer with a thickness of 150 μm was selected as the raw material, and metal was pre-deposited on both sides of the silicon wafer by electrochemical deposition: First, a zinc nitrate solution with a solubility of 3 mol / L was prepared, and the silicon wafer was used as the working electrode. Under the three-electrode system, the concentration of zinc nitrate was 6 mA cm -1 The constant current deposition was carried out for 600s at a current of

[0081] S2. Preparation of amorphous carbon / zinc oxide / silicon / zinc oxide / amorphous carbon intermediate: using chemical vapor deposition to uniformly grow an amorphous carbon layer on the surface of the precursor metal substrate prepared in step S1. The pyrolytic carbon source of the amorphous carbon is camphor balls. The camphor balls and the precursor are placed in the upper and middle heating furnace chambers respectively. During the introduction of a hydrogen-argon mixed gas with a flow rate ratio of 1:8, the reaction is carried out at 1000°C for 16 hours. The thickness of the conductive carbon layer on the surface of the zinc oxide layer is 800nm.

[0082] S3. Constructing an amorphous carbon-silicon-amorphous carbon hollow structure: The intermediate prepared in step S2 was subjected to acid etching treatment using a 5 mol / L nitric acid solution, and the intermediate was immersed in the nitric acid solution for 12 hours to remove the zinc oxide layer in the middle interlayer, and then the composite silicon-based material of this embodiment was prepared by centrifugation. It was measured that the buffer spacing between the amorphous carbon layer and the silicon base body was 1.2 μm.

[0083] Example A4

[0084] This embodiment provides a composite silicon-based material and a preparation method thereof. The composite silicon-based material includes a silicon wafer and a graphene layer bonded to two surfaces of the silicon wafer, forming a sandwich structure of graphitized carbon layer / silicon wafer / graphitized carbon layer, and the graphitized carbon layer is bonded to the surface of the silicon wafer, and a buffer space is formed between the two.

[0085] The method for preparing the composite silicon-based material comprises the following steps:

[0086] S1. Preparation of Fe / Si / Fe precursor: A silicon wafer with a thickness of 80 μm was selected as the raw material, and metal pre-deposition was performed on both sides of the silicon wafer by cathode magnetron sputtering: a Φ50 mm iron sheet was selected as the target material, the target-substrate distance was 90 mm, and the vacuum degree was 5×10 -4 Pa, the working gas pressure (Ar) is 4.5 Pa, the DC power supply sputtering power is 30 W, the sputtering time is 300 s, and the thickness of the pre-deposited iron layer is 100 μm.

[0087] S2. Preparation of graphitized carbon / iron / silicon / iron / graphitized carbon intermediate: A graphitized carbon layer is uniformly grown on the surface of the precursor metal substrate prepared in step S1 by spray pyrolysis. The pyrolysis carbon source of the graphitized carbon is polystyrene. During the introduction of a hydrogen-argon mixed gas with a flow rate ratio of 1:6, acetylene gas with a flow rate of 50 mm / Hg is introduced at the same time. The precursor is placed in the middle of a tubular furnace chamber and reacted at 1200°C for 15 hours; the thickness of the conductive carbon layer on the surface of the iron layer is 500 nm.

[0088] S3. Constructing a graphitized carbon-silicon-graphitized carbon hollow structure: The intermediate prepared in step S2 was subjected to acid etching treatment using 4 mol / L phosphoric acid, and the intermediate was immersed in sulfuric acid for 16 hours to remove the thin iron layer in the middle interlayer, and then the composite silicon-based material of this embodiment was prepared by centrifugation. It was measured that the thickness of the buffer space between the graphitized carbon layer and the silicon base body was 1 μm.

[0089] Comparative Example A1

[0090] This comparative example provides a composite silicon-based material and a preparation method thereof. The composite silicon-based material includes a silicon wafer and a graphene layer bonded to two surfaces of the silicon wafer, forming a sandwich structure of graphene layer / silicon wafer / graphene layer. Compared with the composite silicon-based material in Example A1, the graphene layer is tightly bonded to the surface of the silicon wafer, that is, there is no buffer space between the graphene layer and the silicon wafer.

[0091] Comparative Example A2

[0092] This comparative example provides a silicon-carbon composite electrode material. The carbon composite electrode material comprises silicon particles and a carbon coating layer coated on the surface of the silicon particles. The silicon-carbon composite electrode material is prepared according to the following method:

[0093] After the silicon-based powder and glucose powder are evenly mixed by ball milling at a molar ratio of 20:1, they are transferred to a hydrothermal reactor for hydrothermal reaction at 200℃ for 12 hours, and then centrifuged and washed to obtain the silicon-carbon composite electrode material. However, since there is no obvious buffer layer between silicon and carbon, during the charge and discharge process, the volume expansion effect of silicon will cause the silicon to expand and completely separate from the carbon layer, and the composite effect will completely fail, and the capacity of the electrode will rapidly decay.

[0094] 2. Lithium-ion battery example:

[0095] The present embodiment B1 to embodiment B4 and comparative examples B1 to comparative examples B2 provide a lithium ion battery respectively. Each lithium ion battery is assembled into a lithium ion battery according to the following method:

[0096] 1) Positive electrode:

[0097] NMP: LiFePO4: Super P: PVDF were mixed in a mass ratio of 100:93:2:3, the mixing method was ball milling, and the ball milling time was 60 minutes; the rotation speed was set to 30 Hz; after the operations of homogenization-coating-drying-cutting, the positive electrode sheet was prepared, and the positive electrode sheet was baked in a vacuum oven at 100°C to remove trace water.

[0098] 2) Negative electrode sheet: The composite silicon-based materials provided in Examples A1 to A6 and Comparative Examples A1 to A2 are respectively cut into negative electrode sheets.

[0099] 3) Diaphragm: Use polyethylene (PE) diaphragm.

[0100] 4) Electrolyte: The electrolyte is a 1 mol / L LiPF6 solution, and the solvent is composed of EC (ethylene carbonate) and DEC (diethyl carbonate) in a volume ratio of 1:1.

[0101] 5) Assembly of secondary batteries:

[0102] The positive electrode sheet, negative electrode sheet, electrolyte and separator are assembled into a lithium-ion soft-pack battery according to the lithium-ion battery assembly requirements.

[0103] 3 Lithium-ion battery electrochemical performance:

[0104] The electrochemical properties of the lithium secondary batteries in Examples B1 to B4 and Comparative Examples B1 to B2 were tested under the following test conditions:

[0105] The relevant electrochemical performance test results of the lithium secondary battery are shown in Table 1 below.

[0106] Table 1

[0107]

[0108] The battery rate curves and cycle curves provided in Example B1 and Comparative Example B1 are as follows: Figure 4 and Figure 5 As shown in Table 1 and Figure 4 and Figure 5 It can be seen that the composite silicon-based material of the present application can effectively improve the electrochemical performance of the silicon electrode, and can be stabilized at about 80% after 500 cycles. However, the comparative documents 1 and 2 are only simply carbon-coated. In addition to improving the cycling stability and coulombic efficiency of the electrode to a certain extent in the early stage, the capacity decay is still serious under long cycles. This is mainly because the tight coating leaves no buffer space between silicon and carbon. The serious silicon volume expansion effect under long-term cycles will cause the carbon layer to rupture, and the composite effect cannot be achieved.

[0109] The above embodiments only express several implementation methods of the present application, and the descriptions thereof are relatively specific and detailed, but they cannot be understood as limiting the scope of the present application. It should be pointed out that, for a person of ordinary skill in the art, several modifications and improvements can be made without departing from the concept of the present application, and these all belong to the protection scope of the present application. Therefore, the protection scope of the present application shall be subject to the attached claims.

Claims

1. A composite silicon-based material, characterized in that: The invention comprises a silicon base body and a conductive carbon layer, wherein the conductive carbon layer is bonded to the surface of the silicon base body, and a buffer space is formed between the silicon base body and the conductive carbon layer; along the vertical direction between the conductive carbon layer and the surface of the silicon base body, the thickness of the buffer space is 50 nm-5 μm, and the thickness of the conductive carbon layer is 50 nm-5 μm; The silicon base body has two opposite surfaces, and the conductive carbon layer is bonded to the two surfaces.

2. The composite silicon-based material according to claim 1, characterized in that: The silicon base body is a silicon substrate, and the conductive carbon layer is respectively bonded to two opposite surfaces of the silicon substrate; and / or The silicon matrix and the conductive carbon layer are combined through the van der Waals force and surface tension between the relative surfaces of the two.

3. The composite silicon-based material according to claim 2, characterized in that: The thickness of the silicon substrate is 5-200 μm.

4. The composite silicon-based material according to any one of claims 1 to 3, characterized in that: The material of the silicon base body includes at least one of silicon and silicon-based oxide; and / or The material of the conductive carbon layer includes at least one of graphene, amorphous carbon, carbon nanotubes and graphite carbon.

5. The method for preparing a composite silicon-based material according to any one of claims 1 to 4, characterized in that: The steps include: Providing a silicon base body; forming a film layer on the surface of the silicon substrate; forming a conductive carbon layer on the outer surface of the film layer; The film layer is removed, so that the conductive carbon layer is combined on the surface of the silicon base body, and a buffer space is formed between the conductive carbon layer and the silicon base body, thereby obtaining a composite silicon-based material.

6. The preparation method according to claim 5, characterized in that: The material of the film layer includes any one of metal and metal oxide; and / or The thickness of the film layer is 5-200 μm; and / or The silicon substrate has two opposite surfaces, and the film layer is formed on at least one of the surfaces; The method of forming the conductive carbon layer on the outer surface of the film layer includes at least one of chemical vapor deposition and pyrolysis spraying.

7. The preparation method according to claim 6, characterized in that: The method for forming the conductive carbon layer on the outer surface of the film layer is a chemical vapor deposition method, comprising the following steps: The precursor carbon source is subjected to thermal cracking treatment to generate carbon, and the conductive carbon layer is in-situ grown on the outer surface of the film layer to form the conductive carbon layer.

8. The preparation method according to claim 7, characterized in that: The precursor carbon source includes at least one of methane, ethylene, acetylene, ethanol, benzene, toluene, polymethyl methacrylate, polypropylene, polyethylene, polystyrene, and polyethylene glycol; and / or The precursor carbon source is introduced into the thermal cracking environment together with the carrier gas, and the flow rate of the precursor carbon source is 50-400 mm / Hg; and / or The distance between the precursor carbon source at the thermal cracking treatment site and the surface of the film layer is 15-25 cm; and / or The in-situ growth to form the conductive carbon layer is performed at a temperature of 700-1200° C. and a time of 0.5-6 h.

9. The preparation method according to any one of claims 6 to 8, characterized in that: The film layer is a metal or metal oxide layer, and the method of forming the film layer on the surface of the silicon substrate includes at least one of cathode magnetron sputtering, plasma spraying, chemical vapor deposition, and electrochemical deposition; and / or The film layer is a metal or metal oxide layer, and the method for removing the film layer includes acid etching.

10. A negative electrode, characterized in that: The invention comprises the composite silicon-based material according to any one of claims 1 to 4 or the composite silicon-based material prepared by the preparation method according to any one of claims 5 to 9.

11. A secondary battery comprising a negative electrode, characterized in that: The negative electrode is the negative electrode according to claim 10.

Citation Information

Patent Citations

  • Silicon-based composite material with nano hierarchical structure and preparation method and application of silicon-based composite material with nano hierarchical structure

    CN108023074A

  • Preparation method of silicon-based negative electrode active material, silicon-based negative electrode active material, lithium ion battery negative electrode material and lithium ion battery

    CN108598413A